Diabetes alters myelin lipid profile in rat cerebral cortex: Protective effects of dihydroprogesterone. Issue 168 (April 2017) - Cermenati, Gaia; Giatti, Silvia; Audano, Matteo; Pesaresi, Marzia; Spezzano, Roberto; Caruso, Donatella; Mitro, Nico; Melcangi, Roberto Cosimo
Highlights: Diabetes significantly alters the lipid profile of cerebral cortex myelin. Effects are independent from a blunted endogenous lipid synthesis. Dihydroprogesterone counteracts the diabetes effects on the myelin lipid profile. Abstract: Due to the emerging association of diabetes with several psychiatric and neurodegenerative events, the evaluation of the effects of this pathology on the brain function has now a high priority in biomedical research. In particular, the effects of diabetes on myelin compartment have been poorly taken into consideration. To this purpose, we performed a deep lipidomic analysis of cortical myelin in the streptozotocin-induced diabetic rat model. In male rats three months of diabetes induced an extensive alterations in levels of phosphatidylcholines and phosphatidylethanolamines (the main species present in myelin membranes), plasmalogens as well as phosphatidylinositols and phosphatidylserines. In addition, the levels of cholesterol and myelin basic protein were also decreased. Because these lipids exert important functional and structural roles in the myelin compartment, our data indicate that cerebral cortex myelin is severely compromised in diabetic status. Treatment for one-month with a metabolite of progesterone, dihydroprogesterone, restored the lipid and protein myelin profiles to the levels observed in non-diabetic animals. These data suggest the potential of therapeutic efficacy of DHP to restore myelin in the diabetic brain.